ANALISA PENYEBAB MASALAH MAHASISWA MENGGUNAKAN COHESIVE DEVICES DALAM MENULIS TEKS ANALITIKAL EKSPOSISI - Aprida irma yana; Lollo Rosa Lubis (Jurnal Education and Development, 2019)
This research aims to explain the factors of the students’ causes problems in using cohesive devices in writing analytical expository text, they are reference, substitution, ellipsis, conjunction and lexical cohesion. This research is a kind of qualitative method which is purposed to understand the factors that causes of students’ problems. The data were the fourth semester students of English department of Institut Pendidikan Tapanuli Selatan. The sample were consisting of 40 students. The technique in getting sample was total sampling. The finding shows that the quality of students’ writing was in the level of low category. They have problems in using cohesive devices. The problems are related to the use of reference, substitution, ellipsis, conjunction and lexical cohesion. The reason of the problems in using cohesive devices in writing is based on linguistic, pragmatic, cognitive and cultural factor. Four of them give influence that causes the lack cohesive writing. Therefore, an intensive attention should be given by the lecture to facilitate the students to practice writing in the classroom and do peer correction.